Reticulospinal and corticospinal responses in long-term strength-trained and untrained adults - Meghan Tanel; Dawson J. Kidgell; Sakari Vekki; Juha P. Ahtiainen; Gonzalo Gomez-Guerrero; Eeli J. Halonen; Stuart N. Baker; Simon Walker (European Journal of Applied Physiology, 2025)
Purpose Studies investigating neural adaptation to strength training have yet to determine the loci of previously observed improvements in motor pathway function. While transcranial magnetic stimulation (TMS) studies have typically focused on the corticospinal tract, recent evidence from primates suggests that the subcortical reticulospinal tract may be the primary candidate for adaptation. Methods: Using a cross-sectional comparison, long-term strength-trained athletes ( n = 15, 11M/4F, 32 ± 6 y) and untrained adults ( n = 18, 11M/7F, 32 ± 4 y) underwent a series of neurophysiological tests designed to target corticospinal and reticulospinal functioning based on biceps brachii muscle responses. The StartReact test was used to determine reaction time, rate of torque development, and muscle activity in response to visual (V), visual–auditory (VA, 80 dB), and visual–startle (VS, 120 dB) cues. Reaction times were used to calculate reticulospinal gain ([V–VS]/[V–VA]). Neuro-navigated monophasic TMS to the motor cortex was given during low-force level isometric voluntary contractions (10% of maximum) with both posterior–anterior (100–180% active motor threshold) and anterior–posterior currents (120% active motor threshold). Motor evoked potentials (MEPs) from stimuli given at 120% active motor threshold were compared to startle cue-conditioned responses and anterior–posterior current responses. Results: Untrained adults benefitted more from StartReact (reticulospinal gain, p = 0.003), whereas strength-trained athletes showed greater MEP size at higher stimulation intensities (180% active motor threshold, p = 0.048, 140–180% area-under-the-curve, p = 0.020) and shorter silent period (180% active motor threshold, p = 0.035). Conclusions: Evidence provided here suggests greater cortico-reticulospinal excitability/functioning in long-term strength-trained athletes.

Assay of measles virus IgM and IgG class antibodies by use of peroxidase-labelled viral antigens - J. Salonen; R. Vainionpää; P. Halonen (Archives of Virology, 1986)

Hemagglutinin of vesicular stomatitis virus - P. Arstila; P. Halonen; A. Salmi (Archives of Virology, 1969)

A follow-up study of immunity in children vaccinated with live attenuated measles virus vaccine - P. Halonen; P. Forssell; A. Backman (Archives of Virology, 1965)

Etude de la stabilite de l'antigene poliomyelitique dans le vaccin tetravalent - M. Lamy; P. Halonen (Antonie van Leeuwenhoek, 1962)